Corporate judicial dissolution in China. Issue 2 (6th May 2021) - Lin, Shaowei
Abstract: Corporate judicial dissolution was formally introduced into Chinese Company Law in 2005, and yet there has been scant academic research exploring the function and implications of this procedure. This paper aims to rectify this by offering a comprehensive empirical study of the practice. Research shows that the procedure has been increasingly exercised by shareholders, though the total number of such cases is relatively small. The research also revealed many flaws in the procedure, which is not surprising; teething troubles are all but inevitable for a new procedure. The study also reveals that the courts do not strictly follow the relevant provisions of the Company Law and Judicial Interpretations when adjudicating judicial dissolution cases. Instead, Chinese judges appear to have created their own specific rules, a practice that runs counter to China's current legal system. Finally, this article proposes that the shareholder oppression could be introduced and enacted as one of the grounds to initiate the judicial dissolution.